PENERAPAN LOGIKA FUZZY INFERENCE SYSTEM MAMDANI UNTUK MENENTUKAN KONDISI LINGKUNGAN RUANG STUDI KASUS PT. TELEKOMUNIKASI INDONESIA WITEL BEKASI - Silvy Amelia; warsino . (JURNAL GAUNG INFORMATIKA, 2019)
People will be capable of performing their good if supported by good working environment. The state of the environment a less well may be demanded of time andenergy more which is certainly not support procures design working system efficient and productive. In planning and design working system attention should be given to any factor that could be affect the work environment as, temperature, moisture, lighting, and noise.Methods used in research this is the method fuzzy inference system mamdani. This method used to determine environmental conditions in the work where to known each range of four variables that were used to know space good working for employees. By using the method fuzzy inference mamdani system can be seen that conditions of temperature that is less than 200c , moisture 52.5 % , lighting 200 lux , noise 47.5 then by using the method fuzzy inference system mamdani with the help of the application of matlab then obtained the results of employee performance 90,7. With he knew the environmental conditions study good will be able to know the state of the study employees so that will yield energy good for the environment of the company by therefore digunakanlah the tools to determine a decision by using matlab 2010b.